Displasias cérvico uterinas y su relación con la infección por virus del papiloma humano. Seguimiento de casos - López Galván, Jesús Alejandro (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
Background- Human papilloma virus (HPV) infection is considered necessary to develop cervical cancer causative agent. It is used as method of screening, cytology endocervical, used as screening endocervical cytology and confirms for the diagnosis by colposcopy and cervix biopsy. Objective. - Determining the relationship with the Dysplasias UMF No. 80 human papilloma virus infection. Material and methods. - A descriptive, transversal and observational study was performed. Revised clinical records of women made the DOCaCu with positive result in infection with HPV, dysplasia or cancer from 01 January to 31 December 2008. Results. - Age is 42.05 ± DE; first time taking cytology 29 (50.9%); IVSA greater frequency with 18 (31.6%) and 12 (21.1%) at the age of 18 and 20 respectively; the number of sexual partners dominance of one sexual partner 39 (68.4%); with 2 and 3 pregnancies with a frequency of 11 (19.3%) and 13 (22.8%); positive smoking 13 (22.8%) patients; final diagnose of cervico vaginitis, negative malignancy or negative HPV infection with 22 (38.6%), HSIL with a frequency of 19 (33.3%) patients, LSIL with 14 (24.6%) patients and invasive carcinoma in 2 (3.5%) patients. The association to HPV infection was 19 (33.3%). Conclusions. - The prevalence of intraepithelial lesions was 0.53%. Frequency of HPV infection in relation to intraepithelial lesions was 33.3%.

La infección por virus del papiloma humano (VPH) se considera agente causal necesario para desarrollar cáncer cérvico uterino. El programa encargado a nivel nacional, emplea como tamizaje la citología endocervical y corrobora el diagnóstico por colposcopía y biopsia del cérvix. Objetivo.- Determinar la relación de infección por virus del papiloma humano con las Displasias en la UMF No. 80. Material y métodos.- Se realizó un estudio observacional, transversal, descriptivo. Se revisaron los expedientes clínicos de las mujeres que se realizaron la DOCaCu con resultado positivo a infección por VPH, displasia y/o cáncer del 01 de enero al 31 de diciembre del 2008. Resultados.- Edad media de 42.05 ± DE; primera vez que se tomaban citología 29 (50.9%); IVSA mayor frecuencia con 18 (31.6 %) y 12 (21.1 %) en 18 y 20 años respectivamente; número de parejas sexuales predominó 1 pareja sexual con 39 (68.4 %); con 2 y 3 embarazos frecuencia de 11 (19.3 %) y 13 (22.8 %); tabaquismo positivo en 13 (22.8%); en el diagnostico final predominó cervicovaginitis, negativa a malignidad o negativa a infección por VPH con 22 (38.6%); la LIE-AG con 19 (33.3%); LIE-BG con 14 (24.6%) y carcinoma invasor en 2 (3.5%). La asociación a Infección por VPH fue en 19 (33.3%). Conclusiones.- La prevalencia de lesiones intraepiteliales fue de 0.53%. Frecuencia de infección por VPH en relación con las lesiones intraepiteliales fue de 33.3%.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4209; info:eu-repo/classification/cti/3; FCMB-E-2014-0268; Citología de cérvix; Colposcopía; Biopsia